Perencanaan Arsitektur Enterprise Menggunakan TOGAF ADM Pada MTS Darul Ulum Durian Luncuk Kabupaten Batanghari - Dea Maharani; Sharipuddin; hartiwi, Yessi (LPPM Universitas Dinamika Bangsa, 2024)
Abstract− MTS Darul Ulum Durian Luncuk Batanghari district, is one of the private MTS in the Durian Luncuk area, Batanghari district. Where the existing systems in each field are assisted by using microsofr word and microsoft excel in data processing but have not been integrated between on field an another. So that data cannod be used together in one field or between other fields and cause the required data and information to be inappropriate because of the difficulty of accessing data and information. Then te researcher proposes an enterprise architecture plan for MTS Darul Ulum Durian Lncuk Batanghari district using TOGAF ADM, because TOGAF ADM is not only a framework but also provides the process steps used in enterprise modeling which proposes systematic steps in planning enterprise architecture which consists of several phase namely, vision architecture, business architecture, information system architecture and technology architecture. From the discussion above the authors propose 9 applications that can be developed to support the organization’s business strategy at MTS Darul Ulum Durian Luncuk Batanghari district.